Gas-solid fluidization modification of calcium carbonate for high-performance poly (butylene adipate-co-terephthalate) (PBAT) composites - Shang, Jinzhi; Li, Chang; Song, Yang; Yan, Mingkai; Li, Lin; Hu, Chaoquan (Frontiers in Chemistry, 2023)
Modifying biodegradable poly (butylene adipate-co-terephthalate) (PBAT) plastic with inorganic fillers is critical for improving its overall performance, lowering the costs, and expanding its application scope. The chemical modification method for the inorganic filler determines the application performance of PBAT composites. In this work, gas—solid fluidization method was developed as a simple, efficient, and scalable strategy for chemically modifying CaCO3 filler. The modified CaCO3 filler was mixed with PBAT and melt extruded to prepare biodegradable PBAT/CaCO3 composites. The characterization results show that gas—solid fluidization method combines the traditional wet modification method’s excellent modification effect with the scalability of the traditional dry modification method. The effects of modification methods and amount of CaCO3 filling on the crystallinity, mechanical, and rheological properties of PBAT/CaCO3 composites were compared. The results demonstrated that PBAT/CaCO3 composites containing 30% gas—solid fluidization modified CaCO3 could still maintain excellent overall performance. As a result, this work provides a simple, efficient, and scalable method for chemically modifying inorganic fillers and preparing biodegradable composites.